2023
DOI: 10.3389/fvets.2023.1110801
|View full text |Cite
|
Sign up to set email alerts
|

Production performance, egg quality, and uterine gene expression for layers as affected by N-Carbamylglutamate supplementation

Abstract: IntroductionSupplementation of exogenous additives is a strategy to improve laying performance of layers by regulating uterine function. N-Carbamylglutamate (NCG) as an activator for endogenous arginine synthesis has the potential to regulate the laying performance of layers, but its effects have not been fully understood.MethodsThis study investigated the effects of dietary supplementation of NCG on production performance, egg quality, and uterine gene expression in layers. A total of 360 45-week-old layers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Given the low NAG activity in the intestines of piglets, post-weaning arginine requirements often remain inadequately fulfilled, rendering arginine an essential amino acid for piglets [12]. Research conducted on poultry has indicated that NCG can enhance the performance and egg quality as well as the antioxidant capacity of laying hens [13,14]. Studies using NCG in weaned piglets have found that NCG may promote intestinal growth and improve growth performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the low NAG activity in the intestines of piglets, post-weaning arginine requirements often remain inadequately fulfilled, rendering arginine an essential amino acid for piglets [12]. Research conducted on poultry has indicated that NCG can enhance the performance and egg quality as well as the antioxidant capacity of laying hens [13,14]. Studies using NCG in weaned piglets have found that NCG may promote intestinal growth and improve growth performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…By entering the mitochondria and activating the key enzyme carbamoyl phosphate synthase-1 in the urea cycle, NCG accelerates citrulline synthesis and promotes endogenous arginine production (6). In monogastric animals, NCG supplementation has been reported to improve growth and reproductive performance (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%